Enhancing physical performance in elite junior tennis players with a caffeinated energy drink - Gallo-Salazar, C.; Areces, F.; Abian-Vicen, J.; Lara, B.; Jose Salinero, J.; Gonzalez-Millan, C.; Portillo, J.; Munoz, V.; Juarez, D.; Del Coso, J. (International Journal of Sports Physiology and Performance, 2015)
The aim of this study was to investigate the effectiveness of a caffeinated energy drink to enhance physical performance in elite junior tennis players. In 2 different sessions separated by 1 wk, 14 young (16 ± 1 y) elite-level tennis players ingested 3 mg caffeine per kg body mass in the form of an energy drink or the same drink without caffeine (placebo). After 60 min, participants performed a handgrip-strength test, a maximal-velocity serving test, and an 8 × 15-m sprint test and then played a simulated singles match (best of 3 sets). Instantaneous running speed during the matches was assessed using global positioning (GPS) devices. Furthermore, the matches were videotaped and notated afterward. In comparison with the placebo drink, the ingestion of the caffeinated energy drink increased handgrip force by ~4.2% ± 7.2% (P = .03) in both hands, the running pace at high intensity (46.7 ± 28.5 vs 63.3 ± 27.7 m/h, P = .02), and the number of sprints (12.1 ± 1.7 vs 13.2 ± 1.7, P = .05) during the simulated match. There was a tendency for increased maximal running velocity during the sprint test (22.3 ± 2.0 vs 22.9 ± 2.1 km/h, P = .07) and higher percentage of points won on service with the caffeinated energy drink (49.7% ± 9.8% vs 56.4% ± 10.0%, P = .07) in comparison with the placebo drink. The energy drink did not improve ball velocity during the serving test (42.6 ± 4.8 vs 42.7 ± 5.0 m/s, P = .49). The preexercise ingestion of caffeinated energy drinks was effective to enhance some aspects of physical performance of elite junior tennis players.